Pakistan, to the future with hope - Khan, D. Shah.; Sustainable Development Policy Institute (Lahore : Vanguard, 1998)
Papers presented at the Second Annual Sustainable Development Conference organised by the Sustainable Development Policy Institute in Islamabad, August 4-9, 1996.
0
Keywords: MCE; Sustainable development -- Pakistan